A Phenomenological Study: Understanding Registered Nurses Experiences Related to Dysfunctional Leadership in a Hospital Setting - Roter, Annette B. (Journal of Organizational Psychology, 2016)
This phenomenological research study explored the experience so Registered Nurses exposed to perceived dysfunctional leadership behaviors. The study provides insights into the phenomenon and how participants of the study were able to cope and adapt to the experience. Four major themes emerged from the research: 1.) The dysfunctional leader’s approach to leading, 2.) The dysfunctional leader’s competence and leadership attributes, 3.) The organization’s competence related to addressing dysfunctional behaviors and 4.) The emerging of the phenomenon; the experiences of Registered Nurses exposed to dysfunctional leadership behaviors and how they made sense of their experiences